Teaching Information Retrieval With Web-based Interactive Visualization - Brusilovsky, Peter; Ahn, Jae-wook; Rasmussen, Edie (Journal of education for library and information science, 2010)
Interactive visualization is a powerful educational tool, which has been used to enhance the teaching of various subjects from computer science to chemistry to engineering.This paper describes the use of interactive visualization tools in the context of a graduate course in information retrieval, to demonstrate two well-known retrieval models, the Boolean model and the vector space model. The results of five classroom studies with these tools are reported. The impact of the tools on student learning, as well as student attitudes toward the tools, were investigated. The results of the classroom studies indicate that use of interactive visualization in a homework context can result in significant growth of knowledge. The majority of the students recognize the value of interactive visualization and recommend its use in the context of information retrieval courses. The study also demonstrated that visualization focusing on less known and harder to understand topics causes a larger growth of knowledge and is perceived as more useful. This result suggests placing higher priority on the development of visualization tools for harder to understand topics.